PENERAPAN MEDIA POWTOON PADA PEMBELAJARAN MATERI PERUBAHAN WUJUD BENDA TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS III - Amilia, Sintia; Rahayu, Dewi Widiana; Ibrahim, Muslimin; Rulyansah, Afib (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to determine the extent to which powtoon animation learning media can influence student learning outcomes on material changes in the shape of objects in class III SDN Kertajaya IV/210 Surabaya. This research uses quantitative research with pre-experimental method one group pretest posttest. The data collection technique used was observation and pretest posttest. This study uses SPSS 25.0. Based on the results of the t-test analysis of the average pretest of 64.37 and the average posttest value of 87,25 and the sig. (2-tailed) or a test of 0,01 which means <0,05 indicates that Ho is rejected and Ha is accepted. While the results of the percentage of pretest scores of students who meet the minimum completeness criteria (> 75) from the data it can be seen that of the 24 respondents who completed the work only 7 students and those who did not complete as many as 17 students and the results of the percentage value of the posttest it is known that students who meet the completeness criteria minimum (> 75) as many as 22 students from 24 students. This study shows that there is a significant effect of animated videos on student learning outcomes at SDN Kertajaya IV/210 Surabaya.